The association between intolerance of uncertainty and Internet addiction during the second wave of the coronavirus disease 2019 pandemic: A multiple mediation model considering depression and risk perception. Issue 3 (6th April 2022) - Luo, Ronglei; Li, Qi; Meng, Guangteng; Zheng, Ya; Hu, Kesong; Zhang, Xiaoya; Dai, Bibing; Liu, Xun
Abstract: Repeated outbreaks of coronavirus disease 2019 (COVID‐19) have forced people to shift most of their work and life activities from offline to online, leading to a growing problem of Internet dependence and even Internet addiction. However, the mechanism of the association between COVID‐19‐related intolerance of uncertainty (COVID‐19 IU) and Internet addiction during the second wave of COVID‐19 is still unclear. The current study explored the association between COVID‐19 IU and Internet addiction as mediated by depression and risk perception based on the Uncertainty‐Depression‐Perception‐Addiction model (UDPA). A total of 1, 137 adult participants were recruited, and COVID‐19 IU, depression, risk perception, Internet addiction, and demographic variables were analyzed. The results showed that COVID‐19 IU was significantly and positively associated with Internet addiction and that this relationship was mediated in parallel by depression and risk perception. Our findings further extend the Interaction of Person‐Affect‐Cognition‐Execution (I‐PACE) model from the perspective of applicability in the unique context of COVID‐19. Furthermore, the study suggests that individuals could decrease their dependence on the Internet to prevent Internet addiction during the second wave of the pandemic through effective interventions that include lowering COVID‐19 IU, improving emotion regulation, and developing reasonable perceptions of risk.